Causal analysis of carbon emissions, deadweight tonnage of global shipping fleet, fuel oil consumption, and economic activities in marine transportation. Issue 4 (2nd April 2016) - Chang, Ching-Chih
ABSTRACT: This paper examines the dynamic causal relationships between carbon emissions, deadweight tonnage (DWT) of the total global shipping fleet, fuel oil consumption, and economic activities for marine transportation using cointegration, error-correction, and Granger causality techniques. The intensity of carbon emissions and energy consumption, in addition to the elasticity of emissions and DWT, is discussed. It is concluded that (1) there exist long-run relationships between these variables for the period of 1980 and 2006; (2) the higher levels of economic activities induce more DWT growth than the growth of emissions; and (3) the fuel oil consumption is a weak exogenous variable to produce the emissions. This paper also found that the cost of mitigation is increasing, and thus carbon finance is likely to become more common in the future. These results also provide policy recommendations to combat climate change.